Mere discipleship : radical Christianity in a rebellious world - Camp, Lee C. (Grand Rapids, Mich. : Brazos Press, 2008)
In the clear and compelling fashion of C.S. Lewis's classic Mere Christianity, Lee Camp here sets forth his vision of what it means to truly follow Christ in the twenty-first century. Drawing on a sound biblical framework of what disciples believe and therefore what they should do, Camp challenges Christians to put obedience to Jesus as Lord ahead of allegiances to all earthly authorities--be they nationalistic, political, economic, or cultural. To Camp, that means loving one's enemies, not killing them; evangelizing by showing Jesus, not just talking about him; and allowing God's grace to transform one's notions of wealth. This substantially revised and expanded second edition updates examples, adds chapter introductions and summaries, and includes an extensive study guide and a reading guide. - Publisher.
Part I : Reenvisioning discipleship -- "Radical" discipleship -- God's way of working -- Pledging allegiance to the Kingdom of God -- Part II : What disciples believe -- The Gospel : repent, for the Kingdom is at hand -- The Savior : the Slaughtered Lamb -- The church : the body of Christ -- Part III : What disciples do -- Worship : why disciples love their enemies -- Baptism : why disciples don't make good Americans (or Germans or Frenchmen) -- Prayer : why disciples trust God rather than their own calculations -- Communion : why disciples share their wealth -- Evangelism : how disciples "make a difference" -- Study guide / by Joshua J. Graves.
Includes bibliographical references and index.
Keywords: Christianity -- Essence, genius, nature; Mission of the church; Spiritual formation; Discipling (Christianity)